2013
DOI: 10.1007/s11010-013-1638-2
|View full text |Cite
|
Sign up to set email alerts
|

ER stress and ASK1-JNK activation contribute to oridonin-induced apoptosis and growth inhibition in cultured human hepatoblastoma HuH-6 cells

Abstract: Oridonin, the main active component of Rabdosia rubescens, has antitumor activities in experimental and clinical settings. The aims of the current study were to explore the anticancer abilities of oridonin in hepatoblastoma (HB) HuH-6 cells and to investigate the underlying mechanisms. We found that oridonin inhibited HuH-6 cell in vitro growth in a dose- and time-dependent manner. Further, oridonin induced HuH-6 cell apoptosis and G2/M cell cycle arrest. Upon studying the mechanism, we found that oridonin tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…ROS can trigger the activation of redox-sensitive signal transduction and MAPK pathways that regulate cellular mechanisms of cell survival, death, and immunity (9,30,31). MAPKs including ERK, p38 MAPK, and JNK are key components of signaling pathways that control cell differentiation and growth (9,30,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ROS can trigger the activation of redox-sensitive signal transduction and MAPK pathways that regulate cellular mechanisms of cell survival, death, and immunity (9,30,31). MAPKs including ERK, p38 MAPK, and JNK are key components of signaling pathways that control cell differentiation and growth (9,30,31).…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs including ERK, p38 MAPK, and JNK are key components of signaling pathways that control cell differentiation and growth (9,30,31). There is evidence that MAPKs can be phosphorylated and activated in response to oxidant-induced alterations of the redox state (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an orally available drug, oridonin is demonstrated to have anti-cancer activities in multiple cancers over the past decades, including leukemia, lymphoma, osteosarcoma, myeloma, uveal melanoma, neuroblastoma, hepatocellular, laryngeal, esophageal, and oral squamous cell carcinoma, lung, colorectal, breast, gastric, pancreatic, and prostatic cancers [543][544][545][546][547][548][549][550][551][552][553][554][555][556][557][558]. The anti-cancer effects of oridonin are shown in many aspects, including the induction of cell apoptosis, autophagy, cell cycle arrest, and the suppression of angiogenesis, cell migration, invasion and adhesion [554,[559][560][561][562][563][564].…”
Section: Oridoninmentioning
confidence: 99%
“…1), is a diterpenoid compound (10). Previous studies have shown that oridonin has antitumor activities in vivo and in vitro (11)(12)(13), and oridonin inhibited proliferation of cancer cells by inducing autophagic pathways (14)(15)(16)(17)(18), arresting the cell cycle on G 0 /G 1 phase (19) or G 2 /M phase (20)(21)(22)(23)(24), inducing apoptosis of human laryngeal cancer cells (25), esophageal cancer (26), colorectal carcinoma (27), pancreatic cancer (28), hepato cellular carcinoma (29,30). However, few reports exist on oridonin-induced apoptosis on gastric cancer.…”
Section: Introductionmentioning
confidence: 99%